Pengaruh Media Permainan Tebak Kata Dalam Meningkatkan Minat Belajar Bahasa Arab Siswa Kelas V Mi Al Iman Sorogenen Tahun Ajaran 2023/2024 - Syukmi Muniratul Kamalia; Sihono; Banat Su'adini Sabrina (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze the effect of using the word-guessing game as an instructional medium on the Arabic learning interest of fifth-grade students at MI Al Iman Sorogenen in the 2023/2024 academic year. The research employed an experimental method with a pretest-posttest control group design. All 20 students of the fifth grade were involved as research subjects. Data were collected through observation, interviews, questionnaires, and documentation, and were then analyzed descriptively using SPSS version 25. The results revealed that there was no significant effect of the word-guessing game on increasing students’ interest in learning Arabic, as indicated by a significance value of 0.104 (p > 0.05). These findings suggest that further investigation into instructional media innovations is necessary to enhance students’ interest in learning Arabic at the elementary school level.